Graphical representation of stress and work - Wildin, George Washington (My University, 1892)
Introduction: By graphical representation of “stress” and “work”, we mean representation of lives that is take for instance the different members or pieces which compose a bridge or roof truss. Knowing the total load in which the truss is subjected, a diagram is obtained, showing the direction, magnitude, and kind of stress to which each member is subjected. The answer to the problem in question is obtained in simple lives placed directly before the eye where it can be comprehended in all its relations. This method for the solution of problems is not a new one, but it is almost wholly unknown to the masses. The more prominent mathematicians and engineers have labored hard to introduce the method into practice, and at present ever have only a fair foothold. The ease, accuracy, and speed with which complex problems are solved, and the limited amount of mathematical knowledge and skill required in their solution, are points which specially favor this method and cannot help but give it prominence over the more common method of solving problems by means of long and intricate formulas.
Citation: Wildin, George Washington. Graphical representation of stress and work. Senior thesis, Kansas State Agricultural College, 1892.
Morse Department of Special Collections
Keywords: Statistics; Stress; Work; I/O; Neurology; Theses; Manuscripts (documents)